Clinical features at the time of non-hysteroscopic myomectomy before pregnancy, which affect adverse pregnancy outcomes: a retrospective cohort study - Young Ran Kim; Eun Duc Na; Jae Eun Jung; Ji Hyun Moon; Ji Yeon Lee (BMC, 2022)
Abstract Background To investigate the association of clinical characteristics at the time of non-hysteroscopic myomectomy before pregnancy and adverse obstetric outcomes in the next pregnancy. Methods In this retrospective cohort study, we identified 248 women who underwent abdominal or laparoscopic myomectomy for intramural (IM) and/or subserosal (SS) uterine myomas in Bundang CHA Medical Center before pregnancy and delivered at the same hospital between 2010 and 2020. The association between clinical characteristics at the time of myomectomy and subsequent obstetric outcomes was analyzed using the Chi-square test, the Student t-test or one-way ANOVA, and multivariable analysis. Results There was one case of uterine rupture. The gestational age at delivery was 37.7 ± 2.4 weeks. There were 2 (0.8%) cases of fetal loss before 23 weeks, but there were no cases of perinatal death. The risk of transfusion during or after delivery was higher in the group in which multiple myomas were removed compared to the group in which only one was removed (aOR = 2.41, 95% CI [1.20-4.86], p = 0.014). The risk of neonatal composite morbidity was higher in the group in which myomas including the IM type were removed, than in the group in which only SS myomas were removed (aOR = 14.29, 95% CI [1.82-99.57], p = 0.012). Although not statistically significant, the group in which the sum of the diameters of the three largest myomas was greater than 15 cm showed a higher frequency of preterm birth (19.3% vs. 10.1%, p = 0.001) and lower birth weight (2901 ± 625 g vs. 3063 ± 576 g, p = 0.001) compared to the group with diameters less than 15 cm. Placenta accreta/increta (7.9% vs. 3.8%, p = 0.043) and lower placental weight (646 ± 170 g vs. 750 ± 232 g, p = 0.034) were more common in patients with an interval between myomectomy and pregnancy of less than 12 months compared to more than 12 months. Conclusions To our knowledge, this is the first study to investigate the association between clinical features at the time of myomectomy before pregnancy and various adverse obstetric and perinatal outcomes. If the removed myomas are multiple, IM, large, or the interval between myomectomy and pregnancy is short, the risk of obstetric and neonatal complications may increase.